Grameen Microfinance And Sustainable Empowerment: A Study Of Farmerettes In Jobra Village, Bangladesh - Saima, Sorna Umme (2024)
In the rural setting of Jobra village in Bangladesh, female farmers rely on microfinancing loans from Grameen Bank, and face challenges in achieving sustainability, hindering their empowerment efforts. Therefore, this study aims to identify the sustainability issues farmerettes are facing in Jobra villages, Bangladesh, from Grameen Bank microfinancing loans; and analyse the effect of Grameen Bank’s loan on sustainable empowerment of farmerettes in Jobra Village. The study involves 14 farmerettes and two community leaders as respondents. Primary data was collected through semi-structured interviews and analysed using ATLAS.ti software. To examine the issues and effects of Grameen's sustainable empowerment, the study adopts the Capability Approach framework, which centres on the dimensions of Agency, Resources, and Achievements within Collective Empowerment. The findings of the study reveal a significant reliance on Grameen loans, coupled with inadequate bank supervision and training, a cascading impact of mission drift on borrowers, and a tendency towards loan misuse. Consequently, the identified issues lead to economic, social, political, and psychological disempowerment effects among farmerettes, underscoring the need for a holistic microfinance approach addressing multidimensional empowerment for sustainable development. The study concludes by recommending future research to develop and implement strategies for a comprehensive microfinance model, emphasizing that such efforts can contribute to a holistic approach and foster sustainable empowerment for farmerettes in rural Bangladesh.